PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN TARUNA BARU AKADEMI ANGKATAN LAUT MENGGUNAKAN METODE FUZZY - Islami, Fajrul (Jurnal Ekobistek, 2013)
Navy of the Republic of Indonesia one part of the military has the responsibility to enforce the law and maintain the security of the sea forces and national jurisdiction in accordance with international law. In carrying out the duties and responsibilities of the Navy to be supported cadetmidshipmen are tough and smart. Therefore, in creating a formidable cadets, prospective cadets are given training through the Naval Academy. Education conducted to prepare the cadets to be a leader and is the backbone and driving force of the Navy. The existence of inaccuracy in delivering value to prospective cadets have an impact on the decision given less precise. Therefore, to facilitate in the selection of candidates for naval cadets, Decision Support Systems can be an option in choosing a new cadet at the Naval Academy. With fuzzy methods of the tests performed can be used as a variable that will be used as a judgment in a decision Keywords: Naval Academy midshipmen, fuzzy logic method, Tahani models and decision support system